Panduratin A mitigates inflammation and oxidative stress in DSS-induced colitis mice model - Abdelrahim Alqudah; Esam Qnais; Omar Gammoh; Yousra Bseiso; Mohammed Wedyan; Muna Oqal (Future Science OA, 2024)
Aim This study explored Panduratin A’s protective effects against DSS-induced colitis in mice, focusing on reducing inflammation and oxidative stress in the colon.Methods Mice were treated with dextran sodium sulfate (DSS) and Panduratin A (3, 6, 18 mg/kg), and changes in body weight, colon length, Disease Activity Index (DAI), histopathology, inflammation markers including tumor necrosis factor- α (TNF-α), Interleukin-1 β (IL-1β), Myeloperoxidase (MPO), and oxidative stress, Malondialdehyde (MDA) were evaluated.Results Panduratin A significantly reversed DSS-induced symptoms, including body weight loss, colonic length shortening, and DAI increase, while reducing histopathological damage. It lowered inflammatory markers and oxidative stress, suppressed NF-κB activation, and enhanced Nrf2 and HO-1 expression.Conclusion Panduratin A shows promise as a colitis treatment, warranting further research for broader clinical application.